Meningkatkan Kemampuan Mengenal Angka Melalui Permainan Pohon Angka Pada Anak Usia 5-6 Tahun - Meri Diana; Citra Ayu; Putri Asilestari (LPPI Yayasan Almahmudi bin Dahlan, 2024)
This study is motivated by the low ability of children in recognising numbers, therefore researchers provide a solution to solve this problem in the form of using number tree media to improve children's ability to recognise numbers. The type of research applied is classroom action research with the aim of improving the learning process and improving learning outcomes, especially improving children's ability to recognise numbers. This research was carried out in two cycles, each cycle of 2 meetings with the stages of planning implementation observation and reflection as specified in the class action research system. The data collection technique used is observation with the instrument observation sheet and documentation to capture events during the research process, while the first data analysis technique is quantitative the data obtained is then analysed quantitatively both from the teacher's activity teaching student learning activities and student learning outcomes after quantitative data analysis is carried out Then further discussed or analysed qualitatively so that the data collected can be interpreted or interpreted clearly. From the implementation of this study, the data resulted in a significant increase from the cycle which was only 33.7% to 58% at the end of cycle 2 and this research was declared successful.